Preparation of N-doped Carbon/Metal Phosphides as Promising Trifunctional Electrocatalysts Toward the OER, ORR and HER - Vílchez-Cózar, Álvaro; Bazaga-García, Montse; Marrero-López, David; Olivera-Pastor, Pascual; Demadis, Konstantinos D.; Cabeza-Díaz, Aurelio; Pérez-Colodrero, Rosario Mercedes (My University, 2022)
Sustainable energy storage and conversion technologies, such as electrochemical water splitting and fuel cells, attracts increasing attention as alternative processes to advance toward a global decarbonation. However, the high cost, scarcity, and poor stability of the most active electrocatalysts, mainly based on noble metal (Pt, RuO2, IrO2,…), difficult severely their large-scale production and use. In this regard, the development of earth-abundant electrocatalysts, with high activity for the different processes, is needed. Several imidazole-containing metal etidronates, MLIm-n (M2+= Fe, Co, Ni and solid solutions; L= ETID; Im= Imidazole; n= [0, 3]), were prepared using different synthetic procedures. Thermal reduction of MLIm-n in 5%H2–Ar at different temperatures resulted on core–shell N-doped carbon/TMPs with variable content of MP and MxP as crystalline phases. Their electrocatalytic activities have been widely studied by cyclic and linear sweep voltammetry, impedance spectroscopy, transmission electron microscopy, and XPS analysis. Preliminary results reveal that factors such as the presence of the imidazole and the metal coordination environment in the precursor samples determine the final composition and electrochemical properties of the resulting pyrolyzed derivatives. So, the Co2+- derivative, CoLIm-0@800, with a composition CoP/Co2P= 80/20 wt. %, exhibited the best electrocatalytic properties toward OER/ORR/HER as well as good capabilities as anode for overall water splitting in comparison to the expensive reference RuO2 electrocatalyst.
Keywords: Oxygen Evolution Reaction (OER); Hydrogen Evolution Reaction (HER); Oxygen Reduction Reaction (ORR); Electrocatalysts; Transition metal phosphides